Soliton transmission through disordered system - Kovalev, A.S.; Prilepsky, J.E.; Gredeskul, S.A.; Derevyanko*, S.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
An exact formula for the probability density of the transmission coefficient through disordered nonlinear soliton-bearing classical one-dimensional system is obtained.